POLITICAL COMMUNICATION OF AGRARIAN REFORM: REPRESENTATION OF THE STATE AND THE PEOPLE IN THE CURRENT OF GLOBAL NEOLIBERALISM - Ahmad Taufan Damanik (Academic Solution Publisher, 2025)
This article analyzes how the state’s political communication constructs and legitimizes agrarian reform discourse within the framework of global neoliberalism. Using a Systematic Literature Review (SLR), the study synthesizes 32 peer-reviewed articles published between 2000 and 2025, selected based on thematic relevance, methodological rigor, and empirical contribution. The analysis identifies a consistent pattern of rhetorical commitment to agrarian justice paired with the material reproduction of land inequality. In particular, the administrations of Susilo Bambang Yudhoyono, Joko Widodo, and Prabowo Subianto have framed land reform as a technocratic process focused on land certification, while avoiding direct confrontation with entrenched elite land ownership. This communication strategy, rooted in hegemonic discourse, has normalized structural exclusion and depoliticized land conflicts. Despite the proliferation of populist slogans, policies remain aligned with corporate and investor interests, marginalizing rural communities and indigenous peoples. The study concludes that political communication in post-authoritarian Indonesia functions not merely as information dissemination but as an ideological tool to maintain elite consensus. Agrarian reform, to be effective, must be reclaimed as a political struggle rooted in participatory justice and grassroots mobilization. Without this shift, reform risks becoming an aesthetic performance rather than a transformative agenda.